Leadership Management of Madrasah Principals in Recruiting New Students at Madrasah Ibtidaiyah - Noviana, Ayu; Imron, I; Mawardi, Imam (Prosiding University Research Colloquium, 2023)
Madrasah leadership management has a very important role in determining the management of school management. Success or failure is influenced by how the principal carries out the management function. Recruitment of students is the process of accepting new students in an educational institution. MI Al-Islam Sutopati 3 is one of the educational institutions that implements the leadership management of the madrasa head in student recruitment. The research method used is a qualitative research method with a descriptive approach. The object of this research is MI Al Islam Sutopati 3. The purpose of this research is to find out how the implementation of the madrasa head's leadership management in the recruitment of students. The results of the study show that MI Al Islam Sutopati 3 applies the management of the madrasa head in accepting new students. The management stages carried out are planning, organizing, actuating, and controlling.